PERUBAHAN SIFAT FISIK TANAH AKIBAT PENGOLAHAN TANAH MINIMUM UNTUK PENANAMAN KEDELAI (Glycine max (L.) Merill) DI LAHAN SAWAH BERIRIGASI - , FRANSISKA MARIA DYAH K, Prof. Dr. Ir. Muhidin Mawardi, M.Eng. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The purpose of this study is to know the quantitative changes in the physical properties of soil as a result from differences soil tillage methods on soybean planting in rice field after rice planting. The experiments were conducted in a randomized complete block design ( RCBD ) in KP4 UGM. Three kinds of treatments are no-tillage (A), once hoe (B) and twice hoe (C) and each treatment was repeated three times . Result of this experiment showed that by once hoe lowering bulk density values by 31 % and increase soil porosity up to 66%, while for twice hoe lowering bulk density values by 36% and increase soil porosity up to 65%. No â tillage treatment retain available moisture better than once hoe and twice hoe treatment. Total yield of soybean in no â tillage treatment didnât have significantly different with once and twice hoe treatment.